Positive effects of running exercise on astrocytes in the medial prefrontal cortex in an animal model of depression. Issue 17 (16th August 2022) - Huang, Dujuan; Xiao, Qian; Tang, Jing; Liang, Xin; Wang, Jin; Hu, Menglan; Jiang, Yanhong; Liu, Li; Qin, Lu; Zhou, Mei; Li, Yue; Zhu, Peilin; et al.
Abstract: Depression is one of the most common mental illnesses and seriously affects all aspects of life. Running exercise has been suggested to prevent or alleviate the occurrence and development of depression; however, the underlying mechanisms of these effects remain unclear. Independent studies have indicated that astrocytes play essential roles and that the medial prefrontal cortex (mPFC) is an important brain region involved in the pathology underlying depression. However, it is unknown whether running exercise achieves antidepressant effects by affecting the number of astrocytes and glutamate transport function in the mPFC. Here, animal models of depression were established using chronic unpredictable stress (CUS), and depression‐like behavior was assessed by the sucrose preference test. After successfully establishing the depression model, experimental animals performed running exercise. Glial fibrillary acidic protein‐positive (GFAP + ) cell number in the mPFC was precisely quantified using immunohistochemical and stereological methods, and the densities of bromodeoxyuridine‐positive (BrdU + ) and BrdU + /GFAP + cells in the mPFC were measured using a semiquantitative immunofluorescence assay. Changes in glutamate transporter gene expression in mPFC astrocytes were detected by mRNA sequencing and qRT–PCR. We found that running exercise reversed CUS‐induced decreases in sucrose preference, increased astrocyte number and the density of newborn astrocytes, and reversed decreases in gene expression levels of GFAP, S100b, and the glutamate transporters GLT‐1 and GLAST in the mPFC of CUS animals. These results suggested that changes in astrocyte number and glutamate transporter function may be potential meditators of the effects of running exercise in the treatment of depression. Abstract : Using immunohistochemical and stereological methods, immunofluorescence assays, RNA sequencing and qRT–PCR techniques, we found that running exercise increased the total number of astrocytes and the density of newborn astrocytes and reversed the changes in the gene expression levels of GFAP, S100b, and the glutamate transporters GLT‐1 and GLAST in the mPFC of CUS animals. Our results suggested that changes in the astrocyte number and glutamate transporter function may be potential meditators of the effects of running exercise in the treatment of depression.